Book review: José Van Dijck, Thomas Poell and Martijn De Waal, The Platform Society: Public Values in a Connective World. Issue 2 (August 2019) - Shipra,
José Van Dijck, Thomas Poell and Martijn De Waal, The Platform Society: Public Values in a Connective World . New York, NY: Oxford University Press, 2018, 226 pp., ₹2652. ISBN 9780190889777 (paperback).